MOTIVASI EKSTRINSIK MAHASISWA KEPERAWATAN SELAMA METODE PEMBELAJARAN BLENDED LEARNING - Adventina Hutapea; Mathilda Sri Melinda; Mila Febiyanti Br. Tinjak; Ruthsela Debora Pasaribu; Peggy Sara Tahulending (Jurnal Keperawatan Priority, 2022)
Blended learning is a learning model that combines face-to-face learning with online learning. The blended learning method has advantages and disadvantages, whether face-to-face learning or online learning. This method must be supported by motivation, such as extrinsic motivation. Extrinsic motivation in blended learning is an encouragement to learn in students which arising from external stimuli to the blended learning method like a social environment, family environment, economic, punishment, gift, and rewards. Based on the survey, nursing students do not agree when blended learning was applied to all courses, because of environmental factors, quotas, networks, devices, and the experience of educators. This study aimed to determine the extrinsic motivation of nursing students during blended learning at the Faculty of Nursing, One of the West Indonesian Private universities. This research was conducted through a quantitative descriptive method. The sampling technique of this research used a simple random sampling method by distributing online questionnaires to the class of 2019 at the Faculty of Nursing was 184 respondents. The data were analyzed using univariate analysis. The result of this study showed that the extrinsic motivation of nursing students during the blended learning at the Faculty of Nursing, one of West Indonesia Private University showed that 139 students (75.5%) with moderate extrinsic motivation category. Based on this result, it is influenced by several indicators of extrinsic motivation such as punishment, rewards, and competition with peers. Further research can focus on the self-motivation of students by comparing intrinsic and extrinsic motivation during blended learning.